ANALISIS PRODUKTIVITAS PRODUKSI DI PERUSAHAAN KECAP MANALAGI DENPASAR - Afifi, Alfiana; Mahatma Tuningrat, Ida Ayu; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September)
Thisresearch aimed to measure and analyze the component which contribute to production productivity of the Perusahaan Kecap Manalagi Denpasar, that produces sweet soy sauce and salty soy sauce. The method used to measure productivity of the company was Objective Matrix (OMAX). There are 6 ratios that have been adapted to the condition of the company; the ratio had already included the criteria of efficiency and effectiveness. The result showed that the highest productivity index level intotal achieved during the measurement on consecutive period of 2014 there were in Juni on 701.9 and the lowest of 149.5 in March.Based on the analysis contribute components of the productivity ratio on the productivity in the production of Perusahaan Kecap Manalagi the highestproductivity value there were in ratio of 5 769.5 and the lowest producitivity value in ratio of 6 468.6.Factors that trigger this low productivity were the performance of the company interms of quality of production and labors are not in a good condition
Keywords: 65,